Supervisi Dan Pengawasan Dalam Pendidikan - Putri Ramasari; Syajida Syajida (Journal Innovation In Education, 2023)
This research was conducted with the aim of examining and evaluating supervision and supervision practices in the educational context at Istiqlal Delitua Private High School. The research method used was interviews with two respondents who were parties involved in the process of supervision and supervision of education at this school. The results of the interviews provide in-depth insight into the effectiveness of supervision, implementation of supervision, supporting programs, actions taken when school principals do not carry out supervision, and the impact of supervision on improving the quality of education. This research was carried out as an assignment in the Educational Administration course under the guidance of Dr. Makmur Syukri, M.Pd.